Dramatic relativistic effects on the ns dipole angular distribution asymmetry parameter, βns, of heavy and superheavy elements. (17th February 2023) - Baral, S; Saha, S; Dubey, K A; Jose, J; Deshmukh, P C; Razavi, A K; Manson, S T
Abstract: A theoretical study of the dipole photoelectron angular distribution asymmetry parameter, β, of the 6s, 5s and 4s subshells has been conducted for a range of closed-shell heavy, Hg ( Z = 80), Rn ( Z = 86), Ra ( Z = 88) and superheavy, No ( Z = 102), Cn ( Z = 112), Og ( Z = 118), Ubn ( Z = 120) elements to understand the deviation of β from the nonrelativistic value of 2 owing to relativistic effects. It was found that the deviation, strongest in Cooper minimum regions, persists over all energy for all ns subshells, and the deviations increase with Z . Three levels of relativistic calculations were performed in order to pinpoint the particular interactions responsible for the details of the behavior of the ns β 's as functions of energy, n, and Z and, in addition to the effects of the (relativistic) spin–orbit interaction, interchannel coupling was found to be of crucial importance in the determination of the β parameter in most of the situations studied.